Kesan pengurusan bencana tsunami akibat penyertaan NGO dan ulama terhadap bantuan serta keterdedahan di Acheh - Muhammad, Mulyagus Usman (2017)
This study is motivated by issues surrounding the victims and community during and after the Tsunamy disaster in Acheh. In order to identify various positive and negative impacts of Tsunami disaster management, two areas that are located in the proximity of Tsunami, the Western Acheh and Simeulue Islands have been chosen. The aim is to investigate the impact of disaster management ensuing from community involvement in the humanitarian aids and their vulnerability in Acheh. It begins with the phases in disaster management and the involvement of NGOs and Muslim scholars. It applies a qualitative approach utilizing ethnography method by collecting data through interviews and observations. 23 people comprising Tsunamy victims, ex-NGO volunteers, muslim scholars and government servants were chosen as samples. NVivo 11, the qualitative data analysis software, was used to analyze the data. The finding reveals four important themes: First, the disaster management theme with 59 references on the effects of early warning, coordination of aids and beneficiaries. The next theme is community engagement with 52 references on the impacts of ommunity empowerment and local wisdom. Thirdly, the humanitarian assistance theme with 44 references on the effects of cash for work and the counseling programme. The fourth theme identifies vulnerability with 47 references on rustiness and shallowness of aqidah. This study has contributed to the establishment of a conceptual framework to be used to guide disaster management in the future. Besides, it can also be a reference to the government of Acheh in managing Tsunami disaster more effectively, especially with the presence of foreign communities and foreign NGOs during the distribution of aids which may not only bring positive, but also negative consequences since it may obscure the sustainability of Islam among the community of Acheh.